2023
DOI: 10.1136/jcp-2023-208810
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology reporting of temporal artery biopsy specimens for giant cell arteritis: results of a modified Delphi study

Abstract: The temporal artery biopsy (TAB) is regarded as the gold-standard test in the diagnosis of giant cell arteritis (GCA). There is a lack of agreement among experienced pathologists regarding the diagnostic features and classification of inflammation observed in TAB sections in the diagnosis of GCA.AimsThe aim of this research study was to establish consensus on the key parameters which should be included in a standardised reporting proforma for TAB specimens. We specifically investigated factors pertaining to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Temporal artery biopsy confirms a pathological diagnosis of GCA; since GCA was originally defined as a pathological construct, a positive biopsy by definition has high face validity as a method for confirming GCA [34]. Pathologists now consider various histological features as consistent with active arteritis [35]. "Healed arteritis" as described by the autopsy studies of Gilmour [3] and Ostberg [7] can sometimes be identified in patients with chronic long-standing disease [36], but the inflammatory infiltrate may persist even after one year of glucocorticoid treatment for GCA [37].…”
Section: Tests To Confirm Gcamentioning
confidence: 99%
“…Temporal artery biopsy confirms a pathological diagnosis of GCA; since GCA was originally defined as a pathological construct, a positive biopsy by definition has high face validity as a method for confirming GCA [34]. Pathologists now consider various histological features as consistent with active arteritis [35]. "Healed arteritis" as described by the autopsy studies of Gilmour [3] and Ostberg [7] can sometimes be identified in patients with chronic long-standing disease [36], but the inflammatory infiltrate may persist even after one year of glucocorticoid treatment for GCA [37].…”
Section: Tests To Confirm Gcamentioning
confidence: 99%